2003
DOI: 10.2298/jsc0301001m
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonding in push-pull 5-substituted-2-alkylidene-4-oxothiazolidines: 1H-MNR spectroscopic study

Abstract: Application of dynamic 1H-NMR spectroscopy added to the understanding of the hydrogen bonds existing in the structurally related 5-substituted-2-alkylidene-4-oxothiazolidines in polar and apolar solvents. The equilibrated mixtures of these typical push-pull alkenes in CDCl3 consist of the intramolecularly H-bonded (E)-isomer and intermolecularly H-bonded (Z)-isomer in varying proportions which depend on the solvent polarity. For the representative of the series (Z)-2-(5-ethoxycarbonylmethyl-4-oxothiazolidin-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
14
1
Order By: Relevance
“…Gilli et al [14][15][16] proposed the concept of RAHBs, this has had great success in many fields such as organic chemistry, [17][18][19][20][21] infrared spectroscopy, 22 nuclear magnetic resonance, 23 electron diffraction, 24 or biological chemistry. [25][26][27][28] The proton donor and proton acceptor groups in RAHBs are connected through a chain of p-conjugated double bonds, and the standard explanation of the noticeable strength of these interactions is based on a chemically intuitive reasoning in which the conjugated bonds display an equalization of lengths through a pseudo-ring.…”
Section: Introductionmentioning
confidence: 99%
“…Gilli et al [14][15][16] proposed the concept of RAHBs, this has had great success in many fields such as organic chemistry, [17][18][19][20][21] infrared spectroscopy, 22 nuclear magnetic resonance, 23 electron diffraction, 24 or biological chemistry. [25][26][27][28] The proton donor and proton acceptor groups in RAHBs are connected through a chain of p-conjugated double bonds, and the standard explanation of the noticeable strength of these interactions is based on a chemically intuitive reasoning in which the conjugated bonds display an equalization of lengths through a pseudo-ring.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were equilibrated at the given temperatures. The 1 H NMR and 13 C NMR data of the configurational isomers (E)-9a and (Z)-9a, fully shown below, provide a fairly complete picture of this isomeric equilibrium. Monitoring of the stereodynamic behaviour associated with the isomerization rate of (E)-9a to (Z)-9a was performed in DMSO-d 6 solutions at 298, 303 and 308 K. The E/Z ratios were determined by the integration of the signals at d 5.64 and d 6.15 ppm, assigned to the C(2 0 )-H protons of (E)-9a and (Z)-9a, respectively.…”
Section: Methodsmentioning
confidence: 88%
“…Recent theoretical studies 10c,i have found that in a fragment shown in Scheme 3, these electronic interactions increase in the order: O o S. In the case of our stereodefined push-pull thiazolidine derivatives 1 (Scheme 1), the above mentioned electronic interactions, that occur here between two electron donors (N ring and S ring ) and one electron acceptor (R 1 CX; R 1 = Ph, OEt, NHPh, NH(CH 2 ) 2 Ph; X = O), have been evidenced by the facile Z/E configurational isomerization that takes place spontaneously in solution, at room temperature (Scheme 4). 11,13 The direction of this isomerization is dictated by solvent polarity. Polar solvents break the intramolecular hydrogen bonding in the E isomer and shift the equilibrium to the Z isomer, by forming stable solventsolute intermolecular interactions.…”
Section: Stereodynamic Behaviour Of 2-alkylidene-4-oxothiazolidine Dementioning
confidence: 99%
See 2 more Smart Citations